2018
DOI: 10.1126/science.aas8954
|View full text |Cite
|
Sign up to set email alerts
|

When did modern humans leave Africa?

Abstract: A ∼180,000-year-old fossil from Israel provides evidence for early forays of Homo sapiens into western Asia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…Archeological evidence puts some temporal boundaries on the times when Neandertals and modern humans might have interacted. The earliest currently known modern human remains outside of Africa is dated to around 188 thousand years ago (ka) ( Hershkovitz et al 2018 ; Stringer and Galway-Witham 2018 ), and the latest Neandertals are suggested to have lived between 37 and 39 ka old ( Higham et al 2014 ; Zilhão et al 2017 ). Thus, the time window where Neandertals and modern humans might have been in the same area stretches over more than 140,000 years.…”
Section: Introductionmentioning
confidence: 99%
“…Archeological evidence puts some temporal boundaries on the times when Neandertals and modern humans might have interacted. The earliest currently known modern human remains outside of Africa is dated to around 188 thousand years ago (ka) ( Hershkovitz et al 2018 ; Stringer and Galway-Witham 2018 ), and the latest Neandertals are suggested to have lived between 37 and 39 ka old ( Higham et al 2014 ; Zilhão et al 2017 ). Thus, the time window where Neandertals and modern humans might have been in the same area stretches over more than 140,000 years.…”
Section: Introductionmentioning
confidence: 99%
“…Ces fossiles ont, par la suite, essentiellement joué un rôle dans les discussions générales sur l'évolution de notre espèce, ses modalités d'expansion et ses migrations jusqu'à la période actuelle [44]. Cro-Magnon n'est-il pas le grandpère des Français dans l'imaginaire collectif ?…”
Section: Discussionunclassified
“…Archaeological evidence puts some temporal boundaries on the times when Neandertals and modern humans might have interacted. The earliest currently known modern human remains outside of Africa are dated to around 188 thousand years ago (kya) (Hershkovitz et al, 2018; Stringer and Galway-Witham, 2018) and the latest Neandertals are suggested to have lived between 37 kya and 39 kya old (Higham et al, 2014; Zilhão et al, 2017). Thus the time window where Neandertals and modern humans might have been in the same area stretches over more than 140,000 years.…”
Section: Introductionmentioning
confidence: 99%